Benchmark code and results for "rhodent: A Python package for analyzing real-time TDDFT response" - Fojt, Jakub; Rossi, Tuomas; Erhart, Paul (Chalmers University of Technology, 2026)
This upload includes benchmark results presented in the article "rhodent: A Python package for analyzing real-time TDDFT response" by Jakub Fojt, Tuomas P. Rossi, and Paul Erhart, as well as the codes to reproduce these results.

See README.md in the upload for a detailed description.
Keywords: Physical Sciences; Fysik